AIDS in the world II : global dimensions, social roots, and responses. The global AIDS policy coalition - Mann, Jonathan M; Tarantola, D (Oxford University Press, 1996)
AIDS in the World, Vol. 1, published in 1992, was the first full analysis of mankind\'s global confrontation with this disease. The AIDS scene, however, spurred by the infusion of enormous monetary allocations, and the participation of thousands of health care professionals, researchers, and social workers, has been changing so rapidly that the need for a second volume was felt much earlier than expected. In AIDS in the World II, the authors extend the international comaprisons from 38 countries to the entire world, and show that the AIDS pandemic has become increasingly fragmented within the world population. They present data that takes the discussion beyond the current understanding of the vulnerability of nations and communities to the worldwide spread of HIV, engaging in a detailed exploration of the social strategies that have enabled individuals to avoid infection. Greater emphasis is placed upon the vulnerabilities of different age and sex groups, such as infants, children and women. AIDS in the World II charts a course into the future based on a clear analysis of the global pandemic and response, the crucial lessons learned from the first decade, and the understanding of the scientific and social dimensions of the HIV challenge. The book explains how the diversity of reactions to the pandemic has contributed to a more specific understanding of the determinants of our vulnerability to HIV/AIDS, and offers a blueprint for an expanded global prevention effort. Intended to serve the information needs of all professionals involved in AIDS research and care, this volume\'s accessibility and clarity of writing also make it appropriate for the general reader.
Keywords: AIDS /syndrom získané imunodeficience/; dermatovenerologie